RECOVERY OF HUMAN DIGINITY; KANTIAN CONSIDERATION - Chinedu Ifeakor; Anselm Ikenna Odo (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2021)
This paper tends to recover the dignity of human person using Kant’s view point. Human dignity has for long being in a state of pang.  It has been in the lowest esteem in the contemporary society; human right abuses, depersonalization of man, and lack of human respect. The researchers adopt expository method in carrying out the work. The researchers conclude that human life is a phenomenon characterized by a high sense of uniqueness. Every human person ought to be properly treated with such uniqueness, bearing in mind that- all are one and the same people.This paper tends to recover the dignity of human person using Kant’s view point. Human dignity has for long being in a state of pang.  It has been in the lowest esteem in the contemporary society; human right abuses, depersonalization of man, and lack of human respect. The researchers adopt expository method in carrying out the work. The researchers conclude that human life is a phenomenon characterized by a high sense of uniqueness. Every human person ought to be properly treated with such uniqueness, bearing in mind that- all are one and the same people. Keywords:Recovery, human person and dignity.